Case Report: Vasospastic angina presenting as phantom odor perception - Zubair, Haroon; Suma, Valentin; Masood, Faisal; Jan, M. Fuad; Bajwa, Tanvir; Haddadian, Babak (Frontiers in Cardiovascular Medicine, 2024)
Background Vasospastic angina usually presents with intermittent episodes of chest pain. It can rarely be associated with the perception of phantom odors. Case summary A 69-year-old woman presented for evaluation of intermittent shortness of breath and chest pain. She reported that she often experienced an abnormal smell sensation just prior to the event. The patient had abnormal smell sensation and shortness of breath at the initiation of exercise stress echocardiography with transient electrocardiographic changes and new regional wall motion abnormalities. Subsequent invasive coronary angiography showed no obstructive epicardial coronary artery disease. The patient was started on calcium channel blocker therapy with resolution of symptoms. Conclusion Phantom odor perception has been rarely reported as an angina-equivalent symptom. Clinicians should have a high index of suspicion in patients presenting with atypical anginal symptoms.